Natural disasters in a two-sector model of endogenous growth - Ryo Horii; Masako Ikefuji (Yale University, Economic Growth Center, 2010)
Using an endogenous growth model with physical and human capital accumulation, this paper considers the sustainability of economic growth when the use of a polluting input (e.g., fossil fuels) intensifies the risk of capital destruction through natural disasters. We find that growth is sustainable only if the tax rate on the polluting input increases over time. The longterm rate of economic growth follows an inverted V-shaped curve relative to the growth rate of the environmental tax, and it is maximized by the least aggressive tax policy from among those that asymptotically eliminate the use of polluting inputs. Moreover, welfare is maximized under an even milder environmental tax policy, especially when the pollutants accumulate gradually.
Keywords: O41; H23; Q54; 330; human capital; global warming; environmental tax; endogenous depreciation; nonbalanced growth path